Cover Crop Mixtures Do Not Use Water Differently than Single‐Species Plantings. (1st May 2015) - Nielsen, David C.; Lyon, Drew J.; Hergert, Gary W.; Higgins, Robert K.; Calderón, Francisco J.; Vigil, Merle F.
Abstract : Recent recommendations advocating the use of cover crop mixtures instead of single‐species in semi‐arid environments require rigorous scientific studies. One of those stated benefits is greatly reduced water use by cover crops grown in mixtures. The objectives of this study were to characterize soil water extraction patterns and determine water use of cover crops grown in single‐species plantings and in a 10‐species mixture and to compare cover crop water use to evaporative water loss from no‐till fallow. The study was conducted at Akron, CO, and Sidney, NE, during the 2012 and 2013 growing seasons on silt loam soils. At each location there were a dryland treatment and an irrigated treatment. Soil water contents were measured by neutron scattering and time‐domain reflectometry at six depths (0.0–1.8 m, Akron) or four or five depths (to 1.2 m or 1.5 m, Sidney). There were no consistent significant differences in soil water contents or growing season crop water use with the single‐species plantings compared with the 10‐species mixture. Cover crop water use (216 mm) averaged 1.78 times greater than evaporative water loss (122 mm) from the no‐till fallow treatment with proso millet ( Panicum miliaceum L.) residue. There appears to be no evidence from data collected in this semi‐arid environment, even when irrigated to simulate higher rainfall environments, to support the conclusion that cover crops grown in multi‐species mixtures use water differently than single species‐plantings of cover crops.